Do romance ao romance histórico: algumas considerações sobre a teoria marxista do romance de György Lukács - Rafael da Rocha Massuia (Ciências Sociais Unisinos)
In the present paper we will discuss, in general terms, the historical and social implications of the analysis performed by the Hungarian Marxist philosopher György Lukács on the novel. For that, we will make a brief resumption of the context of the emergence of his literary-aesthetic work, which emerges with a striking contrast to the previous theories carried out in the field of Marxism on the said theme. In the sequence, we will resume the Lukácsean broader conception of the novel, specially highlighted in the paper “The novel as Bourgeois epic”, published in 1935, and then to delve into the more specific issue of the novel subgenre that combines History and Fiction, recorded in the book The historical novel, published in 1937, both during Lukács’ exile period in the 1930’s on the Soviet Union.